2011
DOI: 10.1371/journal.pone.0015642
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Dependent Thresholds of 10-ns Electric Pulse Induced Plasma Membrane Disruption and Cytotoxicity in Multiple Cell Lines

Abstract: In this study, we determined the LD50 (50% lethal dose) for cell death, and the ED50 (50% of cell population staining positive) for propidium (Pr) iodide uptake, and phosphatidylserine (PS) externalization for several commonly studied cell lines (HeLa, Jurkat, U937, CHO-K1, and GH3) exposed to 10-ns electric pulses (EP). We found that the LD50 varied substantially across the cell lines studied, increasing from 51 J/g for Jurkat to 1861 J/g for HeLa. PS externalized at doses equal or lower than that required fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
63
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

6
1

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 53 publications
6
63
1
Order By: Relevance
“…have shown that acute uptake of PI and externalization of phosphatidylserine are observed at or near the exposures used in this paper, suggesting that the plasma membrane is likely breached and calcium levels within the cell are elevated [17,18]. Future work will couple the results presented in this paper with flow cytometry data at similar time points to correlate membrane damage with OCR increase.…”
mentioning
confidence: 70%
See 3 more Smart Citations
“…have shown that acute uptake of PI and externalization of phosphatidylserine are observed at or near the exposures used in this paper, suggesting that the plasma membrane is likely breached and calcium levels within the cell are elevated [17,18]. Future work will couple the results presented in this paper with flow cytometry data at similar time points to correlate membrane damage with OCR increase.…”
mentioning
confidence: 70%
“…This data strongly suggests that a calcium-dependent mechanism is at play. Previous data published by our group has shown that modulation of the extracellular calcium during exposure caused deleterious effects in Jurkat cells, suggesting that influx of extracellular calcium magnified loss of cell survival [17]. The data was collected at high pulse numbers (100-300), but show that calcium indeed plays a role in cell response to nsPEF.…”
Section: Number Of Pulsesmentioning
confidence: 87%
See 2 more Smart Citations
“…In cells without G q/11 receptors, nsPEF initiated PIP 2 hydrolysis bypassing known physiological mechanisms and, presumably, acting directly on the plasma membrane. Recently, we reported electric field dose-dependent thresholds of nsPEF-induced plasma membrane disruption and nanopore formation in the multiple cell lines, including primary cultured neurons [4,16]. Neuronal cells are especially sensitive to regulation by intracellular phosphoinositide signaling [10,12] and the ability to selectively tune the degree of signaling would be highly beneficial.…”
Section: Electric Field Induced Dose-dependent Pip 2 Depletionmentioning
confidence: 99%